The Cultural Significance of Traditional Food Practices Among the Deori Tribe of Assam (International Journal of Food and Nutritional Sciences, 2022)
The Deori tribe an indigenous community in Assam holds a unique cultural heritage that prominently features traditional food practices. This paper explores the cultural food habits of Deori tribe and influence of modern era on cultural food heritage. The study conducted in Bahgorah village in Lakhimpur District of Assam highlights the traditional methods of food preparation and their role in preserving Deori cultural identity. This paper aims to provide insights into how these food practices contribute to the community's cultural resilience.